2022
DOI: 10.31014/aior.1993.05.01.414
|View full text |Cite
|
Sign up to set email alerts
|

A Ghanaian Study on Multiple Intelligences of Pre-Service Science Teachers in Selected Colleges of Education

Abstract: The Multiple Intelligence (MI) Theory has been recognised for its significance in education. This study aimed to provide a detailed examination of each intelligence and illustrate how different MIs work. The current study seeks to discover and link pre-service science teachers' numerous intellectual domains and learning style profiles. The survey method was used for the study, which included 150 pre-service science teachers. The “multiple intelligence domains inventory for educators” was utilised to collect da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In fact, some researchers have suggested that male teachers are biologically inclined to outperform female teachers in mathematical tasks, especially spatial representation tasks; this better performance influences an overrepresentation of men in STEM professions (Wegemer & Eccles, 2019). According to a study conducted among Ghanaian teachers, male teachers surpass female teachers in mathematical intelligence (Budu et al, 2022). Conversely, Wardat et al (2022) reported that male and female teachers have similar perceptions and opinions about the practice and instruction of mathematics and science.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, some researchers have suggested that male teachers are biologically inclined to outperform female teachers in mathematical tasks, especially spatial representation tasks; this better performance influences an overrepresentation of men in STEM professions (Wegemer & Eccles, 2019). According to a study conducted among Ghanaian teachers, male teachers surpass female teachers in mathematical intelligence (Budu et al, 2022). Conversely, Wardat et al (2022) reported that male and female teachers have similar perceptions and opinions about the practice and instruction of mathematics and science.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In regards to the variables of gender and discipline, studies have looked into the learning styles, personality types, and multiple intelligence domains of pre-service teachers from different fields. The Multiple Intelligences of Pre-Service Science Teachers at Ghanaian Colleges of Education were investigated [14]. Additionally, Kwao and Ankomah [13] looked at multiple intelligences among elementary school students and found that different people have different approaches to learning mathematics.…”
Section: Introductionmentioning
confidence: 99%